Wireless Sensor Networks : Architectures and Protocols - Callaway, Edgar H. (CRC Press [Imprint] Abingdon : Taylor & Francis Group Florence : Taylor & Francis Group [Distributor], 2003)
Annotation Because they provide practical machine-to-machine communication at a very low cost, the popularity of wireless sensor networks is expected to skyrocket in the next few years, duplicating the recent explosion of wireless LANs. Wireless Sensor Networks: Architectures and Protocols describes how to build these networks, from the layers of the communication protocol through the design of network nodes. This overview summarizes the multiple applications of wireless sensor networks, then discusses network device design and the requirements that foster the successful performance of these applications.The book discusses factors affecting network design, including the partitioning of node functions into integrated circuits, low power system design, power sources, and the interaction between antenna selection and product design. It presents design techniques that improve electromagnetic compatibility and reduce damage from electrostatic discharge.The text also describes the design features of the wireless devices themselves, presenting a thorough analysis of the technology that engineers and students need to design and build the many future applications that will incorporate wireless sensor networks.